Face Threatening Acts in Pornography Cases as an Attempt for Revenge On Social Media ‘X’ in Indonesia: A Pragmatic Study - Gania, Frisha Maia; Nani Surnani; Dian Ekawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study is motivated by the increasing cases of the distribution of pornographic content as a form of revenge on social media in Indonesia. The main objective of this study is to reveal the face-threatening actions used by speaker as an attempt to take revenge on the hearer using nonconsensual pornographic content, to reveal the strategies and linguistic characteristics used by the speaker in his threats to the hearer. This study took data from a thread on the social media called ‘X’ which the thread was uploaded as an effort to ask for justice so that the case gets attention and can be processed properly. This study uses a data provision method with literature review and note-taking techniques to record data related to conversations between the perpetrator and the hearer in screenshots uploaded in the thread on X. Data analysis was carried out using a matching method with a contextual approach by identifying language patterns and communication strategies used by the perpetrator in his threats. This study refers to the theory of face-threatening acts by Brown & Levinson, (1987) and the speech acts theory by Searle, (1969) as a conceptual basis. The results of this study are expected to provide a deeper understanding of the linguistic strategies of speaker of the distribution of pornographic content as a tool to threaten and take revenge on hearers. The study provides a descriptive analysis of using nonconsensual pornographic content, revealing threatening acts and strategies used to seek revenge on social media.